Relocation of Greek Myth in Salvador Dali’s Painting Metamorphosis of Narcissus - Sharma, Prakash; Upadhya, Toya Nath (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Critical observation of the surrealistic painting Metamorphosis of Narcissus (1939) by Salvador Dali unfolds his act of relocating the Greek myth of Narcissus in a unique way, which captures the multiple moments in a single painting. The painting beautifully captures Narcissus first in a crouched naked position and then in a transformed form holding an egg symbolizing the source of Narcissus’ germination. At this backdrop, this research paper reveals how Dali has used the paranoiac-critical method, for which he is best known, to expose the transformative quality of Narcissus. It also reveals the multi layered structure of the painting encompassing multiple moments in a single painting by consequently setting a new trend in the history of painting. Based on the qualitative research design, this paper tries to explore the painting by using both primary and secondary data to justify the main claim. Critical ideas related to the paranoiac-critical method developed by Dali himself and ideas related to the timeless value of mythology are crucial for the analytic purpose of the painting. Indeed, the relocation of myth in the painting offers it a prime value exposing its potentiality to tell the complete mythical story in a single painting. Finally, the paper concludes that the painting is successful to relocate the Narcissus myth in it to reveal the universality of myth with its transformative quality. This research can be beneficial to those who are doing research on mythology, art and their unique potentialities.